Adaptasi Ekonomi Rumah Tangga di Desa Sukowiryo Kabupaten Jember melalui Budidaya Tanaman Sayuran secara Vertikultur - Indri Fariroh; Nurul Dwi Novikarumsari; Ratih Apri Utami (Universitas Mataram, 2021)
The paddy-paddy-palawija or paddy-paddy-tobacco cropping pattern is generally cultivated by most of members Hidayah Tani group in Sukowiryo Village, Jelbuk district, Jember. Meanwhile vegetables are rarely cultivated in there. Vegetable cultivation in yard around the house using verticulture is one of the household economic adaptation efforts during pandemic for increasing income. The aim of this community service are provide knowledge and insight about alternative uses of yard around the house for vegetable cultivation using verticulture, improve family welfares, and environmentally sustainable agriculture implementation. The method used in this program are preparation, socialization, training, and evaluation approaches. The results of this program showed that the community was enthusiastic in vegetable cultivation using verticulture, because its efficient built on limited yard, easy and simple to built in, could increase household income if its commercialized, supporting family food security, easy to get healty food, verticulture building is easy to move.